Multidimensional forests: Complexity of forest-based values and livelihoods across Amazonian socio-cultural and geopolitical contexts - Londres, M.; Schmink, M.; Börner, J.; Duchelle, Amy E.; Frey, G.P. (Elsevier, 2023)
Research on the contribution of forests to local livelihoods has so far had a strong focus on quantifying the monetary value of forest-derived products and services. In this paper, we move beyond monetary valuation and integrate the less tangible and sometimes culturally complex dimensions through which forests support local livelihoods. We look at four local contexts in the Brazilian, Bolivian and Ecuadorian Amazon, which differ markedly in terms of their biophysical, sociocultural and geopolitical settings. Combining economic and anthropological data, we used quantitative and qualitative methods, and measures of the ecological impacts of local forest uses. Quantitative analyses drew on datasets from 48 communities, and 510 households, while the qualitative analyses relied on semi-structured interviews with 78 families in 22 communities. Forest-based livelihoods exhibited complex portfolios, diversified production systems, seasonal variation of activities, and different specialization strategies. Beyond a source of subsistence and cash incomes, forests were locally valued by people across all sites in terms of identities, worldviews, territorial attachment, governance, and conservation. Populations with a longer history of interactions with the environment displayed more complex forest-related cultural systems, but even among people who had migrated into the forest in a more recent historical period, forest-based self-cultural identification was evident. At all sites, forests were unanimously recognized as critical to people’s health and wellbeing, despite substantial differences in local histories, policy and market environments. The findings underscore the persistent importance of non-economic values of forests as both Indigenous and non-Indigenous groups constantly adapt their forest and land use practices based on transcultural exchange and changing conditions. A focus on economic value as the rationale for forest conservation disregards the striking resilience of cultural values in promoting forest conservation and use by diverse local and Indigenous communities, especially when supported by favorable policies and markets.